2020
DOI: 10.1016/j.tifs.2020.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 pandemic and food: Present knowledge, risks, consumers fears and safety

Abstract: Background COVID-19 is a pandemic disease that has paralyzed social life and the economy around the world since the end of 2019, and which has so far killed nearly 600,000 people. The rapidity of its spread and the lack of detailed research on the course and methods of transmission significantly impede both its eradication and prevention. Scope and approach Due to the high transmission rate and fatality resulting from COVID-19 disease, the paper focuses on analyzing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 163 publications
(233 reference statements)
2
86
0
1
Order By: Relevance
“…In both cases, salience is lower in the 'mature' cluster with FSMS fully operational. Duda-Chodak, Lukasiewicz, Zięć, Florkiewicz, and Filipiak-Florkiewicz (2020) emphasize risk of indirect transmission that may occur in food company mainly from food contact surfaces as most of the people touch different things besides their face during the day and infected workers (both presymptomatic and asymptomatic) can unknowingly contaminate these surfaces with Covid-19 virus which may be transferred to other workers.…”
Section: Resultsmentioning
confidence: 99%
“…In both cases, salience is lower in the 'mature' cluster with FSMS fully operational. Duda-Chodak, Lukasiewicz, Zięć, Florkiewicz, and Filipiak-Florkiewicz (2020) emphasize risk of indirect transmission that may occur in food company mainly from food contact surfaces as most of the people touch different things besides their face during the day and infected workers (both presymptomatic and asymptomatic) can unknowingly contaminate these surfaces with Covid-19 virus which may be transferred to other workers.…”
Section: Resultsmentioning
confidence: 99%
“…In previous outbreaks caused by SARS-CoV and MERS-CoV, foodborne cases were not reported ( Lacombe, Quintela, Liao, & Wu, 2020 ; Oliamat et al, 2020 Oliamat et al, 2020 ; Rizou, Galanakis, Aldawoud, & Galanakis, 2020 ). However, the transfer of coronavirus by handlers to the food surfaces is conceivable, given the extension of the food chain ( Duda-Chodak, Lukasiewicz, Zięć, Florkiewicz, & Filipiak-Florkiewicz, 2020 ; Olaimat et al, 2020 ).…”
Section: Findings and Implicationsmentioning
confidence: 99%
“…Scientific studies have shown that there are two main routes of transmission of COVID-19: direct (person-to-person touch or inhalation of short-range respiratory droplets) and indirect (airborne and fomite-mediated) [7][8][9]. Individuals may acquire indirect infection by getting into contact with contaminated surfaces and touching their oral, nasal, or ocular mucosal surfaces [10,11].…”
Section: Introductionmentioning
confidence: 99%